Chemical risks from an industrial perspective - Barranco A. (Food safety challenges for mediterranean products, 2015)
I - Introduction II - Chemicals in the food industry III - Food policy IV - Food industry perspective V - Conclusions
Workshop Food Safety Challenges for Mediterranean Products, 2014/06/10-11, Zaragoza (Spain)